A Reproducible I/O Analyzer - Nascimento, Rodrigo P. do; Vel Lejbman, Alfredo Goldman (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2024: Anais da XV Escola Regional de Alto Desempenho de São Paulo, 2024)
This paper presents the Stealth Metrics Framework, an I/O characterization and data-driven I/O replay framework that users can utilize to gain detailed insights into how their applications issue I/O to storage systems. The study provides a clear snapshot of how a MongoDB instance manages recovery from a crash from a storage I/O perspective, and explores potential strategies to enhance recovery performance.